EFFICIENCY OF INVESTMENTS IN THE GREEN ECONOMY TO INCREASE CORPORATE SOCIAL RESPONSIBILITY (INNOVATIVE ECONOMY, 2024)
Zhyvko M.A. EFFICIENCY OF INVESTMENTS IN THE GREEN ECONOMY TO INCREASE CORPORATE SOCIAL RESPONSIBILITYPurpose. The aim of the article is the theoretical substantiation of the tools and methodological apparatus for the effectiveness of investments in the green economy and the intensification of corporate social responsibility.Methodology of research. The methodological basis of the study is based on general scientific methods of scientific knowledge: induction and deduction - at the stage of collecting, systematization and processing of information to identify trends and cause-and-effect relationships in investing in the green economy, and also for increasing corporate social responsibility; analysis and synthesis – to identify the main trends in investing in green technologies; abstract and logical – for summarizing information from various sources and creating a comprehensive view of the investigated problem, forming theoretical conclusions and generalizations; the method of comparativistics – for the analysis of the main vectors of increasing corporate social responsibility and the cause-and-effect relationships between them. The work uses tabular and graphical methods of statistical data processing.Findings. The positive impact on the financial performance of companies through investments in green technologies, which contribute to the reduction of operating costs by increasing energy efficiency and reducing the use of resources, is generalized. The improvement of reputation and relations with stakeholders, through active investment in environmentally friendly technologies, better reputation among consumers, investors and the public, which contributes to increasing trust in the brand and increasing customer loyalty, is substantiated.Risk reduction and increased resilience through investments in the green economy, which help companies reduce environmental and regulatory risks associated with stricter environmental regulations and requirements, are analysed. Social and environmental benefits were identified, as investments in green projects contribute to the creation of new jobs, especially in the areas of renewable energy, waste management and green construction.It was established that increasing the internal efficiency and innovation capacity of companies that invest in green technologies allows them to introduce innovations into their production processes more often, demonstrate greater flexibility and readiness for change, which is an important factor in today's dynamic business environment.Originality. A comprehensive approach to studying the effectiveness of investments in the green economy from the point of view of their impact on corporate social responsibility (CSR) is proposed. A systematic analysis of the relationships between the level of investments in the green economy and CSR indicators of companies was carried out on the basis of a wide range of data from various sectors of the economy, which made it possible to identify key trends and regularities that had not been investigated before.Practical value. Substantiated recommendations for effective investment in green technologies can be used by companies to increase their competitiveness in the market by improving their reputation, strengthening relationships with stakeholders and increasing their innovation capacity.Key words: investments, green economy, corporate social responsibility, green technologies, energy efficiency, waste management, environmentally friendly technologies, innovations.
Keywords: investments; green economy; corporate social responsibility; green technologies; energy efficiency; waste management; environmentally friendly technologies; innovations.